Real-world clinical experience of ticagrelor in Indian patients with acute coronary syndrome after discharge from a tertiary setting - Jain, Dharmendra; Roy, Sanjeeb; Srinivasan, Baskaran; Kumar, Sunil; Wankhede, Shaijesh; Revankar, Santosh; Birla, Ashish (International Journal of Research in Medical Sciences, 2023)
Background: To understand the usage pattern of ticagrelor in real-life clinical experience in Indian patients with the acute coronary syndrome (ACS) after discharge from a tertiary care setting. Methods: A retrospective multicentric observational study conducted across Indian healthcare centers having medical records of adult patients with ACS. Patients prescribed with ticagrelor post-discharge for at least 1 month were included. The study endpoints were to determine the clinical effectiveness of ticagrelor in post-ACS patients and adverse events reported during the study period. Results: A total of 1910 patients with ACS with a mean (SD) age of 58.2 (11.3) years were enrolled in this study. The median (IQR) duration of treatment was 30.0 (30.0-90.0) days. More than half of the patients (n=1115, 58.4%) were managed with interventional therapy. The most common comorbid conditions were type-2 diabetes mellitus (46.9%), followed by hypertension (36.8%). A total of 9.7% of patients reported complaints after treatment with ticagrelor. Among them, weakness, giddiness, and body pain were the most common (3.2%). Conclusions: This real-world study revealed that ticagrelor had been used widely in patients who underwent different management strategies. History of diabetes and hypertension were the most common risk factors. There were no major adverse events reported during the follow-up, indicating ticagrelor is well-tolerated in Indian patients with ACS.